2018
DOI: 10.3389/fcell.2018.00162
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic Functions of MASTL Kinase

Abstract: MASTL kinase is a master regulator of mitosis, essential for ensuring that mitotic substrate phosphorylation is correctly maintained. It achieves this through the phosphorylation of alpha-endosulfine and subsequent inhibition of the tumor suppressor PP2A-B55 phosphatase. In recent years MASTL has also emerged as a novel oncogenic kinase that is upregulated in a number of cancer types, correlating with chromosome instability and poor patient survival. While the chromosome instability is likely directly linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 83 publications
4
29
0
Order By: Relevance
“…Well-differentiated epithelial-like cells have high CNI, whereas low CNI cells have abnormally-shaped nuclei ( Figure 1D). Consistent with the idea that low CNI is a marker of cancer progression and aggressiveness, this score was strongly and negatively associated with the mRNA levels of genes previously implicated in breast tumorigenesis including MCM4 35 , MCM10 36 , FOXM1 37 , CCNE2 38 , and MASTL 39 (Figure 1B). In addition, besides median I1 as an average measure, heterogeneity measures including standard deviation and skewness of morphology scores were also identified in this core network module;…”
Section: Hybrid Network Topological Analysis Revealed Tumour Morpholosupporting
confidence: 83%
“…Well-differentiated epithelial-like cells have high CNI, whereas low CNI cells have abnormally-shaped nuclei ( Figure 1D). Consistent with the idea that low CNI is a marker of cancer progression and aggressiveness, this score was strongly and negatively associated with the mRNA levels of genes previously implicated in breast tumorigenesis including MCM4 35 , MCM10 36 , FOXM1 37 , CCNE2 38 , and MASTL 39 (Figure 1B). In addition, besides median I1 as an average measure, heterogeneity measures including standard deviation and skewness of morphology scores were also identified in this core network module;…”
Section: Hybrid Network Topological Analysis Revealed Tumour Morpholosupporting
confidence: 83%
“…Thus, recent years have seen a growing interest in this area of cell cycle control as a source of potential clinical targets for cancer therapy. Indeed, inhibitors of the Cdk1 regulatory kinases Wee1/Myt1 show promising results in clinical trials , while the PP2A regulatory kinase Greatwall is attracting interest as a potential therapeutic target .…”
Section: The Mitotic Trigger Is An Irreversible Cellular Switchmentioning
confidence: 99%
“…High expression of Greatwall has been associated with poor prognosis in triple‐negative breast cancers and the PP2A regulator B55‐alpha is deleted in 15% of prostate cancers . Current models suggest that PP2A:B55 acts as a tumour suppressor, and cancer cells often employ high levels of Greatwall to downregulate this antiproliferative phosphatase activity . This has been suggested to sensitise cells to loss of Greatwall activity.…”
Section: Mitotic Entry and Cancermentioning
confidence: 99%
“…69 Similar to our group, Rogers et al also showed that MASTL overexpression leads to significant disruption to the members of the Wnt-signaling pathway, including increased phosphorylation of β-catenin and mislocalization of E-cadherin. 23,25 However, the mechanism for MASTL regulation of GSK3β/Wnt signaling is still poorly understood and should be investigated in future studies. Overall, the above studies represent an alluring possibility that MASTL may have other substrates beyond ENSA and regulation of PP2A-B55.…”
Section: Cellular Transformation and Oncogenic Signaling Pathwaysmentioning
confidence: 99%
“…[17][18][19][20] The role of MASTL in regulating mitosis is now well-defined. [20][21][22] Also, a key role of MASTL in oncogenesis has recently been proposed in different cancer types, [23][24][25][26] however, details of the underlying mechanism/s and/or factors regulating MASTL expression/ activity during cancer progression remain unclear and needs detailed molecular investigation. In the light of the critical role of MASTL in cancer progression and unclear knowledge of its cancer promoting role and regulation, we present this review article that summarizes the knowledge from the recent publications regarding the role of MASTL deregulation in cancer progression, mechanism/s by which MASTL promotes tumorigenesis and its efficacy as a novel anticancer therapeutic target.…”
mentioning
confidence: 99%